PENYALAHGUNAAN WEWENANG OLEH PEJABAT PUBLIK DALAM PERSPEKTIF SOSIOLOGI HUKUM (Jurnal Konstituen, 2021)
The purpose of this study is to analyze the abuse of authority by public officials in the perspective of the sociology of law. The form of abuse of authority (detournement de pouvoir) by public officials in the perspective of the sociology of law is a person or public official who is given authority in a position and uses it for personal and group interests with the aim of enriching oneself and certain groups and harming many people or the general public. Sociology of law plays an important role in eradicating abuse of authority (detournement de pouvoir) as a tool/ media for socialization to the public about abuse of authority by people (public officials) in the form of corruption or other actions that are detrimental to the state/ society so that the community can play an important role in overseeing the course of the law. the process of law enforcement so that a sense of justice arises for the community.Keywords: Abuse of Authority, Public Officials, Sociology of Law